Die impak van gepreokkupeerdheid met seksuele aktiwiteit geassosieer met internetgebruik op die gesin - 'n pastorale perspektief - W. Coetzer (Acta Theologica)
Together with the tremendous growth in the number of users of the internet in recent years, there was a corresponding growth in pornographic websites as well as internet sex. According to researchers and counsellors, more and more families and individuals get stuck in this trap, with destructive results for marriages and children. This article focuses on the magnitude of this problem, its progressive character as well as a number of possible causes. Typical behaviour of those addicted to this problem is evaluated as well as the impact of this addiction on sexual intimacy within the marriage. Pastoral guidelines that include a treatment program are discussed and practical hints are suggested. The article is concluded with a number of important websites of organisations that are providing, via the internet, a large quantity of literature and support services.